(untitled) (Analysis in Theory and Applications, 2022)
In this paper we extend the results of [12] to the borderline case s = 12. We obtain the classification of global bounded solutions with asymptotically flat level sets for semilinear nonlocal equations of the type Δ ^12 u=W'(u) inR^n,where W is a double well potential.